UTILIZATION OF THE TIKTOK APPLICATION AS A LEARNING MEDIA TO INCREASE STUDENT ENGAGEMENT IN GRADE IV AT MIN 11 WEST ACEH - Mutia Ulfa; Rina Rahmi (STAI Nusantara Kota Banda Aceh, 2026)
A teacher must be more creative and innovative in applying interesting learning media so that learning conditions do not make students feel bored and boring. This problem needs to be addressed so that learning becomes creative and fun, one of which is by using the TikTok application media to increase student activity in class. This research aims to determine the implementation of the TikTok application as a learning medium to increase the activity of class IV students at MIN 11 West Aceh and to determine the level of student activity by using the TikTok application as a learning medium to increase the activity of class IV students at MIN 11 West Aceh. This research uses an experimental method with test data collection techniques, observation and documentation. The results of the research show that the implementation of the TikTok application as a learning medium to increase the activity of class IV students at MIN 11 West Aceh was carried out in 2 meetings, namely October 26 and October 27 2023. The experimental class observation score was higher than the control class, where the teacher's observation amounting to 88.33% (good) and student observations were in the good category at 88.33% (good). Students are very active in learning by using the TikTok application as a learning medium in class IV at MIN 11 West Aceh. The increase in student activity can be seen from the achievement of student learning outcomes with an average class score of 83.94 and student graduation reaching 87.88%.